‘Egocentricism’ Style or the thematic nub of Zimdancehall? - Saidi, Umali (Midlands State University, 2017)
In Zimdancehall, egocentricism stands out prominent as the hub around which most themes of the songs are knitted on. Prominent Zimdancehall musicians stylistically utilise ‘ego’ defined around their stage names, abilities and celebrated glories in the industry as well as popularity in the country, to craft various themes that ultimately define various messages carried in their songs. Using stylistics, this article critiques selected popular Zimdancehall songs which exhibit the said characteristics showing how some critics have come to conclude that the genre either is bankrupt of in-depth creativity or that a new era of artistry in music has just been born in the country especially when it is drawn in comparison with Sungura or other genres that have been in existence prior to the popularisation of Zimdancehall.